2021
DOI: 10.7759/cureus.13425
|View full text |Cite
|
Sign up to set email alerts
|

Is COVID-19 an Independent Risk Factor for Heparin-Induced Thrombocytopenia?

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes a viral respiratory illness initially described in Wuhan, China, and was declared a pandemic by World Health Organization (WHO) in 2020, and the disease is named coronavirus disease (COVID-19). SARS-CoV2 is known to cause fever, cough, fatigue, and acute respiratory distress syndrome. As more patients become infected, extrapulmonary manifestations came to rise and hypercoagulability is one among those. COVID-19 could predispose patients to bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 16 publications
0
12
0
2
Order By: Relevance
“…Of these, 1,986 were excluded, and 22 full texts were screened for eligibility. Eventually, 15 studies [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] met the eligibility criteria and were included in qualitative synthesis, and 7 studies 29,[32][33][34][35][36]40 were sufficient for quantitative synthesis. Of 7 studies eligible for meta-analysis, the risks of bias were individually assessed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 1,986 were excluded, and 22 full texts were screened for eligibility. Eventually, 15 studies [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] met the eligibility criteria and were included in qualitative synthesis, and 7 studies 29,[32][33][34][35][36]40 were sufficient for quantitative synthesis. Of 7 studies eligible for meta-analysis, the risks of bias were individually assessed.…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics of the 15 included studies (12 published full-texts, 1 fullpreprint report and 2 abstracts) [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] were summarized in Table 1. Across 15 studies (8,053 total patients), there were a total of 40 reported HIT patients.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specificity of platelet factor 4 antibodies has been questioned [ 81 , 86 , 87 ]. Even more so, the concept of heparin-independent genesis of platelet factor 4 antibody during severe COVID-19 has been discussed [ 82 , 85 , 89 ]. Zhu et al provide evidence to drive the hypothesis that anti-Spike RBD antibodies may function in part to activate platelets [ 89 ].…”
Section: Heparin-induced Thrombocytopenia During Covid-19mentioning
confidence: 99%
“…As anticoagulants have been used for both treatment and prevention during COVID-19 especially in advanced illnesses, it is not surprising that eventually there would emerge uncommon citations of heparin-induced thrombocytopenias [76][77][78][79][80][81][82][83][84][85][86][87][88]. Most of the latter, although not all, have been associated with LAC lupus anticoagulant, anti-CL anticardiolipin, anti-ß2 anti-ß2-glycoprotein-I,…”
Section: Heparin-induced Thrombocytopenia During Covid-19mentioning
confidence: 99%